Can physical activity influence the quality of sleep among the elderly? - Podhorecka, Marta; Cytarska, Magdalena; Gębka, Dominika; Perkowski, Radosław; Androsiuk-Perkowska, Joanna; Jaroch, Alina; Siedlecka–Główczewska, Emilia; Sokołowski, Remigiusz; Zukow, Walery; Kędziora-Kornatowska, Kornelia (Journal of Education, Health and Sport, 2017)
<span style="font-size: 12pt; line-height: 175%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-GB">Introduction:<span style="font-size: 12pt; line-height: 175%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-GB"> Research shows that over the half of people in the age of more than fifty have got problems with lowered quality of sleep. The cause of lowered quality of sleep is i.a. waking up early, lengthened sleep latency, increased number of waking during the night or shortened time of sleep. The aim of the study was to show how significant are sleep related problems which appear after the age of fifty and how regular physical activity can improve the quality of sleep and as a result functioning of the elderly. Physical activity delays involutional changes and the process of ageing, which lets the elderly stay independent and self-reliant in everyday activities. <span style="font-size: 12pt; line-height: 175%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-GB">The aim of the study:<span style="font-size: 12pt; line-height: 175%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-GB"> The study was to mark the connection between physical activity intensity and the quality of sleep of the elderly. <span style="font-size: 12pt; line-height: 175%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-GB">Material and methods:<span style="font-size: 12pt; line-height: 175%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-GB"> Research for the study was made by means of anonymous survey which consisted of two questionnaires: The Pittsburgh Sleep Quality Index (PSQI) and The International Physical Activity Questionnaire. The survey was targeted at people in the age of over fifty. 100 people took part in the research. <span style="font-size: 12pt; line-height: 175%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-GB">Results:<span style="font-size: 12pt; line-height: 175%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-GB"> Significant statistical correlation between early falling asleep, waking up at night or before dawn with the intensive or moderate physical effort has been obtained. <span style="font-size: 12pt; line-height: 175%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-GB">Conclusions:<span style="font-size: 12pt; line-height: 175%; font-family: 'Times New Roman', serif; background-image: initial; background-position: initial; background-size: initial; background-repeat: initial; background-attachment: initial; background-origin: initial; background-clip: initial;" lang="EN-GB"> The research has shown that people who performed intense or moderate physical activity woke up less frequently during the night, fell asleep faster and reported better quality of sleep. In addition, it has been noticed that the lowered quality of sleep has got a negative influence on i.a. energy levels and staying alert.